Solvent-dependent hypsochromic shift in the imidazole based complex [Cu(µ2-SO4)(Im)4] and ameliorative effects on breast cancer-induced bone metastases associated oxidative injury in rats - Khouloud Hchicha; Elena Cambiotti; Hmed Ben-Nasr; Daniel Chappard; Matti Haukka; Loredana Latterini; Salem Elkahoui; Arif J. Siddiqui; Mejdi Snoussi; Mohd Adnan; Houcine Naïli; Riadh Badraoui (Arabian Journal of Chemistry, 2023)
A sulfate-bridged complex [Cu(µ2-SO4)(Im)4] (1) was prepared and structurally characterized, where Im: imidazole. The X-ray structure analysis reveals that 1 crystallizes in the monoclinic system with space group C2/c. The octahedral coordination around the metal center is made up of four distinct imine nitrogen atoms in the equatorial plane, and two sulfate oxygen atoms occupying the axial sites. The covalent linkage between metals via the sulfate group, forming infinite 1D zigzag chains, ensures the entanglement of the structure. These chains, in turn, are further assembled into a 2D network through NH⋯O hydrogen bonding. Thermal analyses underline the high thermal stability of our complex, which starts to decompose at 200 °C. The infrared spectrum confirms the results obtained from the crystallographic analysis. Optical studies reveal the presence of a hypsochromic effect noticed in the absorption and photoluminescence spectra. The synthesized compound was found to reduce both oxidative injury and histopathological features, which are associated with skeletal metastases as a result of malignant Walker 256/B breast cancer cells.